2016
DOI: 10.1021/acs.est.6b01796
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Partitioning and Bioaccumulation of Substituted Diphenylamine Antioxidants and Benzotriazole UV Stabilizers in an Urban Creek in Canada

Abstract: Substituted diphenylamine antioxidants (SDPAs) and benzotriazole UV stabilizers (BZT-UVs), previously under reported classes of organic contaminants, were determined in sediment, water, and freshwater biota in an urban creek in Canada. SDPAs and BZT-UVs were frequently detected in all matrices including upstream of the urban area in a rural agricultural/woodlot region, suggesting a ubiquitous presence and bioaccumulation of these emerging contaminants. Spatial comparisons were characterized by higher levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 39 publications
7
100
1
Order By: Relevance
“…The analytical standard 2‐(2H‐benzotriazol‐2‐yl)‐4‐(tert‐butyl)‐6‐(sec‐butyl)phenol (UV‐350) was purchased from BOC Science (purity 97%). Water samples were extracted using solid‐phase extraction (SPE) according to methods previously reported by Lu et al (2016a). The 200‐mg OASIS HLB SPE cartridge was conditioned by 5 mL of 9:1 methyl tert butyl ether:methanol, followed by 8 mL of isopropanol and 10 mL of high‐performance liquid chromatography (HPLC)‐grade water before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical standard 2‐(2H‐benzotriazol‐2‐yl)‐4‐(tert‐butyl)‐6‐(sec‐butyl)phenol (UV‐350) was purchased from BOC Science (purity 97%). Water samples were extracted using solid‐phase extraction (SPE) according to methods previously reported by Lu et al (2016a). The 200‐mg OASIS HLB SPE cartridge was conditioned by 5 mL of 9:1 methyl tert butyl ether:methanol, followed by 8 mL of isopropanol and 10 mL of high‐performance liquid chromatography (HPLC)‐grade water before use.…”
Section: Methodsmentioning
confidence: 99%
“…These levels were similar to or higher than concentrations reported in wastewater and biosolid samples in China (Ruan et al 2012; Song et al 2014) and Europe (Langford et al 2015). Further analyses in fish from eastern Canada revealed that UV‐234 and UV‐328 were present at maximum concentrations of 6.86 and 8.1 ng/g lipid weight, respectively, in hornyhead chub homogenates ( Nocomis biguttatus ), and up to 50.1 and 20.7 ng/g wet weight in the liver of white sucker ( Catostomus commersonii ; Lu et al 2016a, 2017a). Similar and higher concentrations have been reported in other fish species around the globe (Supplemental Data, Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…As shown, many organic substances are not expected to be readily biodegradable using a battery of BIOWIN TM models (USEPA 2012). Field observations of phenolic antioxidants and benzotriazole UV stabilizers in sediments, suspended particles, and fish partly support this (Wang et al 2003;Lu et al 2016;Wick et al 2016), although it is not certain that plastic debris is a significant source of them in the environment. Experimental values are available only for relatively well-studied plasticizers and flame retardants (World Health Organization 1996;Tittlemier et al 2002;Braekevelt et al 2003;Hunziker et al 2004;Kuramochi et al 2007Kuramochi et al , 2014Arnot et al 2009).…”
Section: Organic Additives In Plastic Productsmentioning
confidence: 99%
“…Although experimental studies are lacking on their environmental partitioning, metabolic transformation, and biodegradability, they might accumulate through the marine food chain based on estimated high partition coefficients and low biodegradability. Field observations of phenolic antioxidants and benzotriazole UV stabilizers in sediments, suspended particles, and fish partly support this (Wang et al 2003;Lu et al 2016;Wick et al 2016), although it is not certain that plastic debris is a significant source of them in the environment. Thus, future research should be directed toward those additives that might have persistence, bioaccumulation potentials, and toxicity.…”
Section: Organic Additives In Plastic Productsmentioning
confidence: 99%
“…Up until now, BUVSs have been detected in rivers, lakes and seawater in many countries (eg, China, India, Japan, and Spain) with concentrations ranging from 0.5 to 544.9 ng/L . Most BUVSs are hydrophobic compounds with high octanol‐water partition coefficients (logKow > 4.3), resulting in significant accumulation potentials in suspended matter, sediments, and biota . It is reported that concentrations of BUVSs can reach up to 73 μg/g dry weight in sediments and 316 ng/g lipid weight in fish muscle tissues .…”
Section: Introductionmentioning
confidence: 99%